2014
DOI: 10.1144/sp388.22
|View full text |Cite
|
Sign up to set email alerts
|

Palaeohydrographic reconstructions from strandplains of beach ridges in the Laurentian Great Lakes

Abstract: The current temporal and spatial context of water-level change, drivers of change, and possible future scenarios of the Laurentian Great Lakes is controversial. Palaeohydrographs are being constructed from measured subsurface elevations of palaeo-swash zones and modelled ages in strandplains of beach ridges that are preserved in embayments along the lakes' edge. More than 800 elevations and 200 ages have been collected from 15 strandplains to construct site strandplain palaeohydrographs. Palaeo-beach elevation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…The lake level rise continued to ca. 4.8-4.1 ka at the peak Nipissing elevation in the Lake Superior basin, indicated by age models based on numerous OSL dates on strandplain beach sediments in the basin (Johnston et al 2012(Johnston et al , 2014. Multiple OSL dates of Nipissing beach sediments near Alpena, Michigan, closer to the southern outlet, indicated that the highest Nipissing strand was deposited at 4.5 ka (OSL 4460 6 490) (Thompson et al 2011).…”
Section: Great Lake Nipissingmentioning
confidence: 99%
“…The lake level rise continued to ca. 4.8-4.1 ka at the peak Nipissing elevation in the Lake Superior basin, indicated by age models based on numerous OSL dates on strandplain beach sediments in the basin (Johnston et al 2012(Johnston et al , 2014. Multiple OSL dates of Nipissing beach sediments near Alpena, Michigan, closer to the southern outlet, indicated that the highest Nipissing strand was deposited at 4.5 ka (OSL 4460 6 490) (Thompson et al 2011).…”
Section: Great Lake Nipissingmentioning
confidence: 99%
“…As a consequence, coastal zones in different climatic zones evolve diagnostic features that define zonalities between humid and arid areas and, although not perfectly distributed Overduin et al 2014;6, Forbes et al 2014;7, Martini & Morrison 2014;8, Ruz & Hesp 2014. Temperate: 9, Johnston et al 2014;10, Dashtgard et al 2013;11, Hein et al 2014;12, Bujalesky et al 2013;13, Colombo et al 2014;14, Dillenburg et al 2014;15, Roberts et al 2013;16, Short 2013;17, Costas et al 2013;18, Torres et al 2013;19, Anzidei et al 2014. Subtropic-Tropic: 20, Wallace et al 201421, Scheffers et al 2013;22, Anthony et al 2013;23, Billeaud et al 2013.…”
Section: Energy Distribution and Climatic Zonesmentioning
confidence: 99%
“…Due to their spatial and temporal complexity that results in repeating landform patterns, these chronosequences are particularly well-suited for examining the relationships among the distribution and movement of groundwater (henceforth hydrogeology), the structure and position of coastal landforms (henceforth geomorphology), and the species composition of plant communities. Like dune slacks in coastal marine settings (e.g., Smith et al 2008), sediment deposition in coastal embayments paired with receding sea or lake levels can result in preservation of sandy ridges with intervening swales (Baedke and Thompson 2000;Baedke et al 2004;Johnston et al 2014). Wetlands develop in swales that intersect the water table, leading to arcuate complexes of parallel wetlands, hydrologically connected by the groundwater flow system.…”
Section: Introductionmentioning
confidence: 99%